Reactivity of Copper Complexes with Tripodal Tetradentate Ligands based on Camphoric Acid towards Dioxygen. Issue 22 (13th October 2022) - Stöhr, Fabian; Specht, Pascal; Becker, Jonathan; Göttlich, Richard; Schindler, Siegfried
Abstract: The reaction of dioxygen with copper(I) complexes containing camphor‐derived ligands was investigated. Stopped‐flow measurements revealed the formation of bis( μ ‐oxido) copper complexes at low temperatures. However, these intermediates were not stable enough to be isolated and decomposed quickly. Sterically more demanding alkyl groups slowed the formation of the bis( μ ‐oxido) copper complexes. A kinetic analysis was performed and showed ‐ in line with previous reports ‐ that the rate‐determining step could be assigned to forming a mononuclear superoxido copper complex. For one of the reactions investigated, a product could be structurally characterized and turned out to be a copper(II) complex with an additional hydroxide as a ligand (most likely caused by a C−H abstraction from the solvent acetone). One of the complexes oxidized thioanisole to the corresponding sulfoxide (conversion of 34 % according to GC‐MS) with no byproducts. Chiral GC gave an enantiomeric excess of 14 %. Abstract :